Rates and Quality of Preinterventional Reperfusion in Patients With Direct Access to Endovascular Treatment. Issue 8 (August 2018) - Kaesmacher, Johannes; Giarrusso, Mattia; Zibold, Felix; Mosimann, Pascal J.; Dobrocky, Tomas; Piechowiak, Eike; Bellwald, Sebastian; Arnold, Marcel; Jung, Simon; El-Koussy, Marwan; Mordasini, Pasquale; Gralla, Jan; et al.
Abstract : Background and Purpose—: Preinterventional reperfusion before endovascular treatment (ET) is a benefit of bridging with intravenous tPA (tissue-type plasminogen activator). However, detailed data on reperfusion quality and rates of obviating ET in a cohort of patients with immediate access to ET is lacking. Purpose of this analysis was to evaluate prevalence and quality of preinterventional reperfusion in mothership patients. Methods—: All mothership patients (n=627) from a prospective registry subjected to angiography with an intention to perform ET were reviewed. Preinterventional change of occlusion site (COS) was categorized into COS with Thrombolysis in Cerebral Infarction (TICI) 0/1, COS with TICI ≥2a, COS with TICI ≥2b, and COS with perfusion worsening. Predictors and clinical relevance were evaluated using multivariable logistic regression and results are displayed as adjusted odds ratios (aOR) and corresponding 95% confidence intervals (95% CI). Results—: Prevalence of COS in all patients was 10.7% (95% CI, 8.3%–13.1%), subdividing into 2.7% COS with TICI 0/1, 6.2% COS with ≥TICI 2a (including 2.9% with TICI ≥2b), and 1.8% COS with perfusion worsening. Factors related to COS with ≥TICI 2a were intravenous tPA (aOR, 11.98; 95% CI, 4.5–31.6), cardiogenic thrombus origin (aOR, 2.3; 95% CI, 1.1–4.6), and thrombus length (aOR per 1 mm increase 0.926; 95% CI, 0.87–0.99). Additional ET was performed despite COS with ≥TICI 2a in 51.3%. COS with ≥TICI 2a showed a tendency for favorable outcomes (modified Rankin Scale, ⩽2; aOR, 2.65; 95% CI, 0.98–7.17). Rates of COS with ≥TICI 2a were particularly low in internal carotid artery and proximal M1 occlusions (2.2%; 95% CI, 0.9%–5%), where intravenous tPA was associated with perfusion worsening (aOR, 4.33; 95% CI, 1.12–16.80). Conclusions—: Prevalence of preinterventional reperfusion is non-negligible in patients with direct access to ET and is clearly favored by intravenous tPA treatment. However, it is often incomplete and often requires additional ET. Preinterventional reperfusion of internal carotid artery and proximal M1 occlusions is rare and usually of low quality, where intravenous tPA may also promote perfusion worsening. Abstract : Supplemental Digital Content is available in the text.